Functional interaction between type III-secreted protein IncA of Chlamydophila psittaci and human G3BP1. - Nicole Borth (Public Library of Science (PLoS), 2011)
Chlamydophila (Cp.) psittaci, the causative agent of psittacosis in birds and humans, is the most important zoonotic pathogen of the family Chlamydiaceae. These obligate intracellular bacteria are distinguished by a unique biphasic developmental cycle, which includes proliferation in a membrane-bound compartment termed inclusion. All Chlamydiaceae spp. possess a coding capacity for core components of a Type III secretion apparatus, which mediates specific delivery of anti-host effector proteins either into the chlamydial inclusion membrane or into the cytoplasm of target eukaryotic cells. Here we describe the interaction between Type III-secreted protein IncA of Cp. psittaci and host protein G3BP1 in a yeast two-hybrid system. In GST-pull down and co-immunoprecipitation experiments both in vitro and in vivo interaction between full-length IncA and G3BP1 were shown. Using fluorescence microscopy, the localization of G3BP1 near the inclusion membrane of Cp. psittaci-infected Hep-2 cells was demonstrated. Notably, infection of Hep-2 cells with Cp. psittaci and overexpression of IncA in HEK293 cells led to a decrease in c-Myc protein concentration. This effect could be ascribed to the interaction between IncA and G3BP1 since overexpression of an IncA mutant construct disabled to interact with G3BP1 failed to reduce c-Myc concentration. We hypothesize that lowering the host cell c-Myc protein concentration may be part of a strategy employed by Cp. psittaci to avoid apoptosis and scale down host cell proliferation.